Exploring the antimicrobial potential of chitosan nanoparticles: synthesis, characterization and impact on Pseudomonas aeruginosa virulence factors - Maršík, Dominik; Maťátková, Olga; Kolková, Anna; Masák, Jan (Nanoscale advances, 2024)
The escalating antibiotic resistance observed in bacteria poses a significant threat to society, with the global prevalence of resistant strains of Pseudomonas aeruginosa on the rise. Addressing this challenge necessitates exploring strategies that would complement existing antimicrobial agents, e.g. by substances mitigating bacterial virulence without eliciting selective pressure for resistance emergence. In this respect, free-form chitosan has demonstrated promising efficacy, prompting our investigation into reinforcing its effects through nanoparticle formulations. Our study focuses on the preparation of chitosan nanoparticles under suitable conditions while emphasizing the challenges associated with stability that can affect biological activity. These challenges are mitigated by introducing quaternized chitosan, which ensures colloidal stability in the culture media. Our approach led to the production of trimethylchitosan nanoparticles with a median size of 103 nm, circularity of 0.967, and a charge of 14.9 ± 3.1 mV, stable within a one-month period in a water stock solution, showing promising attributes for further valorization. Furthermore, the study delves into the antimicrobial activity of trimethylchitosan nanoparticles on Pseudomonas aeruginosa and confirms the benefits of both nanoformulation and modification of chitosan, as our prepared nanoparticles inhibit 50% of the bacterial population at concentration ≥160 mg L-1 within tested strains. Additionally, we identified a concentration of 5 mg L-1 that no longer impedes bacterial growth, allowing reliable verification of the effect of the prepared nanoparticles on Pseudomonas aeruginosa virulence factors, including motility, protease activity, hemolytic activity, rhamnolipids, pyocyanin, and biofilm production. Although trimethylchitosan nanoparticles exhibit promise as an effective antibiofilm agent (reducing biofilm development by 50% at concentrations ranging from 80 to 160 mg L-1) their impact on virulence manifestation is likely not directly associated with quorum sensing. Instead, it can probably be attributed to non-specific interactions with the bacterial surface. This exploration provides valuable insights into the potential of quaternized chitosan nanoparticles in addressing Pseudomonas aeruginosa infections and underscores the multifaceted nature of their antimicrobial effects.